From Postcolonial Tourism to Postimperial Melodrama: Fernando Aramburu’s Patria as Spanish Terrorism-Pornography - Gabilondo, Joseba (EGAN, 2021)
JOSEBA GABILONDO. From Postcolonial Tourism to Postimperial Melodrama: Fernando Aramburu’s Patria as Spanish Terrorism-Pornography